Geologi dan Kajian Fasies Gunung Api Purba Soropati Berdasarkan Keberadaan Lava Basal Daerah Gedong dan Sekitarnya, Kecamatan Banyubiru, Kabupaten Semarang, Provinsi Jawa Tengah - Rizqi, Al Hussein Flowers; Maming, Haryadi; Hartono, Hill Gendoet (Retii, 2024)
The study area is located on the flank of Mount Merbabu and south of the Soropati Band. Mount Soropati is thought to be active in the Quaternary, and was formed at the same time as two other nearby volcanoes, Old Merbabu and Ungaran. This study aims to identify basalt lavas on Mount Soropati that spread to the medial facies. The research method used is field observation supported by DEM map analysis and petrographic analysis. On the appearance of the DEM map, Mount Soropati has a morphology that shows the formation of a caldera and a visible depth that is likely the center of volcanic activity on Mount Soropati in the past. Mount Soropati is a Bregada volcano that gathers one Khuluk, Khuluk Telomoyo and one gumuk, Gumuk Gedong. Mount Soropati is composed of basalt lava flows and has historical records of activities that show that Mount Soropati is a polygenetic volcano. Mount Soropati has an effusive type, which is reflected in the Ca-rich plagioclase content, and an explosive type, which can be seen from the former caldera. In volcanic development, Mount Soropati is in the advanced erosional phase. The presence of basalt lava along Â± 2.4 km and a considerable distance from the eruption center may indicate a medial facies.